Analysis of The Implementation of Occupational Health and Safety Management System on Workers Productivity on Structural Finishing Works of Reinforced Concrete Columns - I Made Anom Santiana; I Gede Sastra Wibawa; I Made Tapayasa; I Wayan Suasira; I Ketut Sutapa (Logic : Jurnal Rancang Bangun dan Teknologi, 2018)
The implementation of the project from year to year is significantly improved on implementation aspects of cost, quality, and time, in order to manage the use of human resources to be realistic. Occupational health and safety in a company is often ignored especially for companies which are doing project developments. This also affects the occupational safety of the workers and occupational illness arisen after the projects have been implemented. So in running safe business, occupational health and safety management Systemshould be implemented consistently. The research was conducted in the project of Dialog Villa Petitenget, Cendrawasihstreet, Denpasar, with 15 workers as sample. The implementation of occupational health and safety management systemcan ease the workload of the workers of the structural finishing works of reinforced concrete columns. This is proved by analysis on the treatment group ((p-value< 0.05). This shows that the workloads felt by group P1 (group which implement occupational health and safety management System are lighter than the ones felt by group P0 (group which do not implement the system). The decrease in workload felt by group P1 is 4%. The implementation of occupational health and safety management system can increase work productivity on the construction project of reinforced concrete structure columns. This is proven by the productivity analysis result which shows that the productivity increase experienced by group P1 is 25% with significance level (p-value<0.05). Thus, the implementation of occupational health and safety management system on the structural finishing works of reinforced concrete columns is proven to be able to improve work productivity